Subacute sclerosing panencephalitis: a rare cause of acute cortical visual impairment in an adult. (October 2020) - Herath, HMMTB; Nandasiri, Shanika; Chandrakumara, Amila; Jayamaha, Jude; Senanayake, Sunethra; Goonaratne, Kishara
Adult onset subacute sclerosing panencephalitis (SSPE) after the third decade of life is rare and the manifestations can mimic disorders such as dysmyelinating and metabolic disorders. This case report presents a patient with acute binocular visual impairment in his fifth decade as the first manifestation of SSPE. This is preventable with immunisation against measles. A prior history of measles infection may not be forthcoming in adult onset SSPE. This should be kept in mind as a differential diagnosis when a patient from endemic area presents with acute visual loss even in the absence of classic features. Periodic generalised discharges on the EEG without myoclonus may be seen in this condition rarely as in this case.